2017
DOI: 10.1111/tpj.13520
|View full text |Cite|
|
Sign up to set email alerts
|

Translation regulation in plants: an interesting past, an exciting present and a promising future

Abstract: SUMMARYChanges in gene expression are at the core of most biological processes, from cell differentiation to organ development, including the adaptation of the whole organism to the ever-changing environment. Although the central role of transcriptional regulation is solidly established and the general mechanisms involved in this type of regulation are relatively well understood, it is clear that regulation at a translational level also plays an essential role in modulating gene expression. Despite the large n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
153
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(180 citation statements)
references
References 242 publications
(427 reference statements)
6
153
0
3
Order By: Relevance
“…Synthesis is however only half of the equation governing protein abundance, indeed Arabidopsis has more than 600 F-box proteins as components of diverse E3 ubiquitin ligase complexes that direct protein degradation. Newer evidence has shown that post transcriptional and translational mechanisms (Ponnala et al, 2014;Merchante et al, 2017) and phenomena such as cell-to cell mobile mRNAs (Thieme et al, 2015) and proteins (Han et al, 2014;Guan et al, 2017) play equally important roles in determining the proteome's temporal and spatial plasticity foremost in steady state shifts. Therefore, despite the continued practice of quantifying the abundance of proteins' cognate transcripts to estimate and quantify functional protein coding gene expression, direct, large scale measurement of protein abundance and PTM should be the explicit end point of functional genomics.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis is however only half of the equation governing protein abundance, indeed Arabidopsis has more than 600 F-box proteins as components of diverse E3 ubiquitin ligase complexes that direct protein degradation. Newer evidence has shown that post transcriptional and translational mechanisms (Ponnala et al, 2014;Merchante et al, 2017) and phenomena such as cell-to cell mobile mRNAs (Thieme et al, 2015) and proteins (Han et al, 2014;Guan et al, 2017) play equally important roles in determining the proteome's temporal and spatial plasticity foremost in steady state shifts. Therefore, despite the continued practice of quantifying the abundance of proteins' cognate transcripts to estimate and quantify functional protein coding gene expression, direct, large scale measurement of protein abundance and PTM should be the explicit end point of functional genomics.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis rate is regulated on different levels in response to the energy status of the cell, e.g. via mRNA availability, the GDP and GTP pools, and posttranslational modification of the ribosome (Merchante et al 2017). The two major protein recycling systems in eukaryotes are autophagy and the ubiquitin-proteasome system (reviewed by Dikic 2017, Marshall and Vierstra 2018, Vierstra 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The translation of mRNAs by cytosolic ribosomes into new proteins is dynamically regulated by abiotic environmental conditions such as temperature (Matsuura et al, 2010; Juntawong et al, 2013;Yanguez et al, 2013), oxygen (Branco-Price et al, 2008) and light (Juntawong and Bailey-Serres, 2012;Liu et al, 2012;Missra et al, 2015;Merchante et al, 2017). Both early and more recent studies have highlighted that redox poise and reactive oxygen species can also play important roles in regulating mRNA translation in global and mRNA sequence-specific ways (Tang et al, 2003;Branco-Price et al, 2008;Khandal et al, 2009;Benina et al, 2015).…”
Section: Introductionmentioning
confidence: 99%